Why are reported fair values sticky? - Fischer, Paul; Haushalter, David; Miller, Brian; Pisciotta, Kevin (Review of Accounting Studies, 2026)
Abstract We analyze how incentives affect the reporting of fair values using mutual funds’ valuations of Level 3 equity holdings. We conjecture that the observed stickiness of reported values arises because funds defer revaluation until they can make a sufficiently compelling and objective case to avoid costly accusations of aggressive valuation. Consistent with our conjecture, we find that funds’ revaluations of the same security are clustered in time and tightly distributed, and revaluations of non-traded securities are more likely when market returns are larger and the source of those returns is less subjective. In addition, consistent with a greater concern for overvaluation, we document that funds are more likely to reduce valuations of these holdings when market returns are negative. Finally, given the stickiness of valuations, we provide evidence that funds exploit valuation discretion to improve performance rankings through the timing of revaluations rather than through the levels of new values.